Ratings of affective valence closely track changes in oxygen uptake: Application to high-intensity interval exercise - Roloff, Z. A.; Dicks, N. D.; Krynski, L. M.; Hartman, M. E.; Ekkekakis, P.; Pettitt, R. W. (Performance Enhancement & Health, 2020)
High-intensity interval training (HIIT) may benefit health with low time commitment. High exercise intensity is unpleasant, possibly limiting public health relevance of HIIT. Evidence on affective responses to HIIT protocols is inconsistent. We show that affect closely tracks oxygen uptake during four HIIT protocols. Ratings of affective valence may be useful for monitoring and tailoring exercise load.